2019
DOI: 10.1140/epjds/s13688-019-0184-x
|View full text |Cite
|
Sign up to set email alerts
|

Segregation in religion networks

Abstract: Religious beliefs could facilitate human cooperation [1][2][3][4][5][6], promote civic engagement [7][8][9][10], improve life satisfaction [11][12][13] and even boom economic development [14][15][16]. On the other side, some aspects of religion may lead to regional violence, intergroup conflict and moral prejudice against atheists [17][18][19][20][21][22][23]. Analogous to the separation of races [24], the religious segregation is a major ingredient resulting in increasing alienation, misunderstanding, cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…In particular, the specified issue is relevant for the communities treated by most of the population as "others". It is interesting that the comparative analysis shows that the extent of segregation for different religions is much higher than that for different races and slightly higher than that for different political parties (Hu, Zhang & Zhou, 2019).…”
Section: Cyber Communicationmentioning
confidence: 98%
“…In particular, the specified issue is relevant for the communities treated by most of the population as "others". It is interesting that the comparative analysis shows that the extent of segregation for different religions is much higher than that for different races and slightly higher than that for different political parties (Hu, Zhang & Zhou, 2019).…”
Section: Cyber Communicationmentioning
confidence: 98%
“…A typical research example is how to quantify the religious segregation via analyzing social media data [9]. Religion locates in the core of culture, exhibiting significant positive values like to facilitate human cooperation [10] and to improve life satification [11].…”
Section: Natural Datamentioning
confidence: 99%
“…Questionnaire is not suitable in this scenario because some questions could cause offence. Instead, Hu et al [9] collected publicly available data from weibo.com (one of the largest online social platforms in China, similar to Twitter), where users with religious beliefs are identified by NLP techniques (see details in [9]) and a subgraph induced by these believers is analyzed. Four major conclusions are drawn from such natural data.…”
Section: Natural Datamentioning
confidence: 99%
“…In previous studies, social networks through SNS and cell phones have been extensively investigated, while large-scale face-to-face interaction networks have not been constructed. Large-scale social networks via cell phones and SNS have revealed that people's social connections are related to their economic status [2][3][4][5] and social fragmentation among people with different attributes [6,7]. Universal structural features of social networks have also been investigated such as SNS, e-mail, paper November 23, 2021 1/28 co-authorship networks, and web-based collaboration networks and their scale-free nature is known [8,9].…”
Section: Introductionmentioning
confidence: 99%